Charles Darwin’s The Life of Erasmus Darwin - Harris, Stuart (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2016)
This article addresses the family and intellectual relationship between Charles Darwin and his grandfather Dr Erasmus Darwin. After establishing the publishing history of Charles’s ‘sketch’ of his grandfather’s life, the article shows how Charles approaches his subject by a characteristic biological route: the inheritance of family characteristics. His examination of Erasmus’s life and work establishes inherited talents, especially that for poetry.The biography’s sub-text is to hint at what Charles himself inherited from his grandfather, especially an interest in natural history. However, Charles throughout his earlier life had been very reticent about any impact Erasmus’s writings on biology might have had on his own work. The reticence persists in this sketch and Charles’s focus shifts to Erasmus’s reputation as a poet, and to certain well-known ‘calumnies’ of Erasmus’s character. Charles’s discussion of the poetry reveals as much about himself as it does of Erasmus and the paper concludes with an analysis of Charles’s own poetic taste and literary-critical judgments. The article presents evidence for Charles himself being a highly cultivated reader of poetry and a defender of his grandfather’s reputation as a poet.